N-Glycosylation of Cholera Toxin B Subunit: Serendipity for Novel Plant-Made Vaccines? - Matoba, Nobuyuki (Frontiers in Plant Science, 2015)
The non-toxic B subunit of cholera toxin (CTB) has attracted considerable interests from vaccinologists due to strong mucosal immunomodulatory effects and potential utility as a vaccine scaffold for heterologous antigens. Along with other conventional protein expression systems, various plant species have been used as production hosts for CTB and its fusion proteins. However, it has recently become clear that the protein is N-glycosylated within the endoplasmic reticulum of plant cells—a eukaryotic post-translational modification that is not present in native CTB. While functionally active aglycosylated variants have been successfully engineered to circumvent potential safety and regulatory issues related to glycosylation, this modification may actually provide advantageous characteristics to the protein as a vaccine platform. Based on data from our recent studies, I discuss the unique features of N-glycosylated CTB produced in plants for the development of novel vaccines.